Maxim Of Conversation And Implicature Analysis In Podcast Selena Gomez On: How To Stop Insecurity & Truly Love Yourself To The Core - Wardana, Bima Tri; Budianto, Suhartawan (PT. Gudang Pustaka Cendekia, 2025)
The research made by the author of this thesis aims to analyze the use of conversational maxims and implicatures in Selena Gomez's podcast which discusses the topic “How to Stop Insecurity & Truly Love Yourself to the Core”. The main objective is to understand how conversational maxims and implicatures are applied in the context of podcasts to convey messages about self-confidence and self-love to listeners. The methods used are conversational analysis based on pragmatics theory, conversational analysis based on Grice's (1975), theory of maxims and qualitative methods based on Creswell's (2007), theory then the data analyzed are transcriptions of Selena Gomez podcasts that have been selected based on their relevance to the research topic. The analysis is done by looking at how each conversational maxim (maxims of quantity, quality, relevance, and manner) and the two existing implicatures (conventional implicature and conversational implicature) are applied in the verbal expressions in the podcast. The result is that the four maxims and two implicatures are all found in Selena Gomez's podcast.